Adjuvant Corticosteroid Therapy in Hepatosplenic Candidiasis-Related Iris - Bayram, Cengiz (Università Cattolica del Sacro Cuore, 2012)
Candida infections are the most frequent infections in neutropenic patients. Hepatosplenic candidiasis (HSC) is a part of disseminated Candida infection that occurs most commonly in patients with hematologic malignancies treated with chemotherapy and requires protracted antifungal therapy. During invasive mycosis with rapid resolution of immunosuppression, immune reconstitution inflammatory syndrome (IRIS) which mimics treatment failure, drug toxicity or breakthrough infections may occur. Manifestation period, histopathologic findings and favorable effect of steroids to its inflammatory symptoms strongly suggest that HSC belongs to the invasive fungal infection induced IRIS. We present a child with B cell-acute lymphoblastic leukemia who developed HSC and addition of corticosteroid therapy to antifungal treatment achieved rapid resolution of the clinical symptoms and laboratory findings.